Unveiling Critical Success Factors for Marketing Intelligence : A Multi-Method Framework - Vishnoi, Sushant Kumar; Sharma, Vikram Kumar; Ghosh, Suman Kalyan; Mathur, Smriti; Mittal, Saurabh; Singhal, Rashi; Agarwal, Parul; Jain, Aditi (Prabandhan: Indian Journal of Management, 2026)
Purpose : The purpose of this study was to identify, structure, and examine the causal dominance of critical success factors underlying marketing intelligence using a multi-method analytical framework. Methodology : With reference to the growing importance of marketing intelligence for intelligent marketing, this study conducted an extensive literature review (N = 152) and identified 29 critical success factors of marketing intelligence. Further data was collected (n = 256) for principal component analysis and (n = 13) for employing fuzzy DEMATEL. Findings : The results of principal component analysis segmented the 29 dimensions into 7 corresponding factors. Further, fuzzy DEMATEL (Decision-Making Trial and Evaluation Laboratory) was employed to establish Strategic Marketing Planning (SMP), Strategic Business Intelligence (SBI), Customer Brand Co-Creation (CBC), Tactical Marketing (TM), and Strategic Customer Intelligence (SCI) as cause factors, and Competitive Intelligence Analysis (CIA), Digital Dynamism (DD) as effect factors. Originality : This study offered a novel multi-method investigation by integrating the PRISMA framework, PCA, and Fuzzy DEMATEL to identify cause and effect dimensions and enhance system-level understanding of marketing intelligence implementation.